Evaluation of the kangaroo method during the Covid-19 pandemic in two reference maternity hospitals in Pernambuco - Joice Luiza Alves Cândido; Silvia Wanick Sarinho; Paulo Germano de Frias (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to evaluate the second stage of the Kangaroo Mother Care (KMC) and its integration with the third stage in maternity hospitals in Recife in the context of the coronavirus pandemic. Methods: normative assessment carried out at the Kangaroo Neonatal Intermediate Care Unit (KNICU) in two public reference maternity hospitals for KMC between November/2021 and May/2022. The logical model and matrix of KMC indicators were developed and validated using the Delphi Method: semi-structured interviews were carried out with professionals from the KNICU team and the municipal child health coordination. It was considered implemented when the criteria were met (from 100.0 to 80.0%); partially implemented (79.9 to 60.0%); incipient (59.9 to 40.0%) and not implemented (<or=39.9%). Results: the MC was partially implemented in both KNICU (79.0% both). The Structure dimension was implemented (84.0 and 97.0%) and the Process dimension, in the Education (70.0% both) and Management components, were partially implemented (61.0% and 78.0%), although the units claim that they do not share clinical objectives, exams and treatments and do not have an effective referral/counter-referral system. While Assistance was implemented in one unit (90.0%) and partially implemented in the other (75.0%). Conclusion: KNICU was partially implemented during the coronavirus pandemic in the two reference maternity hospitals, but with obstacles to integration with the third stage of the method.